Graphene Quantum Dots: Green Synthesis, Characterization, and Antioxidant and Antimicrobial Potential - Kadyan, Pooja; Thillai Arasu, Ponnusamy; Kataria, Sudhir Kumar (International Journal of Biomaterials, 2024)
Antibiotic resistance is becoming more common, emphasising the demand for novel antibacterial treatments. The current investigation describes the green synthesis of graphene quantum dots (GQDs) using M. indica leaves and characterization via Fourier-transform infrared spectra (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), and ultraviolet-visible (UV-Vis) spectrophotometer. The results showed that GQDs are spherical in shape. In vitro antioxidant and antimicrobial studies indicate that the biological efficacy of synthesized GQDs was higher than the ethanolic leaf extract. GQDs exhibited the highest scavenging efficacy with lowest IC50 (half-maximal inhibitory concentration) value. However, antimicrobial study showed more inhibitory activity of GQDs against all screened microorganisms, i.e., Staphylococcus aureus, Escherichia coli, Bacillus subtilis, and Pseudomonas aeruginosa, and fungi, i.e., Aspergillus niger and Aspergillus flavus. Graphene quantum dots facilitate reactive oxygen species (ROS) which ultimately lead to antioxidant and antibacterial activity. This approach would provide an efficient alternate method for tackling microorganisms.